A Comparison between two Dolutegravir-Based two-drug Regimens as Switch Strategies in a Multicentre Cohort of HIV-1-Infected Patients. Issue 1 (January 2019) - Ciccullo, Arturo; Baldin, Gianmaria; Capetti, Amedeo; Rusconi, Stefano; Sterrantino, Gaetana; d'Ettorre, Gabriella; Colafigli, Manuela; Modica, Sara; Lagi, Filippo; Giacomelli, Andrea; Cossu, Maria Vittoria; Restelli, Sibilla; et al.
Background: Two-drug regimens are increasingly used in clinical practice as switch strategies. We compared the efficacy and safety of two dolutegravir (DTG)-based dual therapies: DTG plus lamivudine (3TC group) versus DTG plus rilpivirine (RPV group). Methods: In a multicentre cohort of virologically suppressed (HIV RNA <50 copies/ml) HIV+ patients switching to DTG+3TC or DTG+RPV we analysed the incidence of virological failures (VF) and treatment discontinuations (TD), as well as their predictors. Results: We analysed 416 patients, 229 in the 3TC group and 187 in the RPV group. The 3TC group, during 344.4 person-years of follow-up (PYFU), had 10 VF without the emergence of resistance mutations, while 30 patients discontinued the regimen. In the RPV group, during 371.0 PYFU, there were 5 VF (1 developed non-nucleoside reverse transcriptase inhibitor mutations Y181C and E138Q) and 13 TD. The estimated probability of remaining free from VF at 48 weeks showed no significant difference between groups (log-rank 0.172). We found a higher risk of VF in patients with peak viral load >500, 000 copies/ml in both treatment groups (log-rank P =0.004 in each group). The estimated probability of remaining in the study regimen at week 48 was 89.0% with DTG+3TC and 96.1% with DTG+RPV (log-rank 0.015). After adjusting for potential confounders, treatment group was not associated with TD. A significant decrease in total cholesterol was observed at week 48 in both groups while renal function remained unchanged. Conclusions: DTG+RPV and DTG+3TC were compared in populations with different characteristics in clinical practice: both regimens showed good effectiveness and improved lipid profile.